2011
DOI: 10.4161/cc.10.9.15479
|View full text |Cite
|
Sign up to set email alerts
|

Protein phosphatase PP6 is required for homology-directed repair of DNA double-strand breaks

Abstract: DNA double-strand breaks (DSBs) are among the most lethal lesions associated with genome stability which, when destabilized, predisposes organs to cancers. DSBs are primarily fixed either with little fidelity by non-homologous end joining (NHEJ) repair or with high fidelity by homology-directed repair (HDR). The phosphorylated form of H2AX on serine 139 (γ-H2AX) is a marker of DSBs. In this study, we explored if the protein phosphatase PP6 is involved in DSB repair by depletion of its expression in human cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
61
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 34 publications
(54 reference statements)
4
61
0
1
Order By: Relevance
“…The holoenzyme of PP6 is composed of a catalytic subunit, a SAPS domain subunit, and an ankyrin repeat subunit (10). PP6 regulates chromosome segregation in mitosis through inhibiting Aurora A activity (11) and facilitating the repair of DNA double-strand breaks by activating DNA-activated protein kinase (DNA-PK) and dephosphorylating g-H2AX in HeLa cells (12,13). Involvement of PP6 in modulating NF-kB activity is suggested by findings that the PP6 protein interacts with and protects IkBε from TNF-a-induced degradation in Cos7 cells (14).…”
mentioning
confidence: 99%
“…The holoenzyme of PP6 is composed of a catalytic subunit, a SAPS domain subunit, and an ankyrin repeat subunit (10). PP6 regulates chromosome segregation in mitosis through inhibiting Aurora A activity (11) and facilitating the repair of DNA double-strand breaks by activating DNA-activated protein kinase (DNA-PK) and dephosphorylating g-H2AX in HeLa cells (12,13). Involvement of PP6 in modulating NF-kB activity is suggested by findings that the PP6 protein interacts with and protects IkBε from TNF-a-induced degradation in Cos7 cells (14).…”
mentioning
confidence: 99%
“…This appears contradictory to the findings of other reports [99][100][101], in which inhibition of PP6c or PP6R1 expression by siRNA impairs DNA-PK activation in response to IR, though all reports demonstrated that preventing PP6c expression sensitizes tumor cells to IR. Our laboratory further demonstrated that depletion of PP6c or PP6R2, but not PP6R1, compromised repair of CPT-induced DSBs or I-SceI-induced DSB, suggesting that DNA lesions induced by different agents may require different PP6 holoenzymes [102].…”
Section: Pp6mentioning
confidence: 88%
“…PP2A is mainly responsible for H2AX in response to exogenous DNA damage [83]. We and our collaborators have also revealed that H2AX is dephosphorylated by PP6 both in vitro and in vivo [99,102]. Silencing of either PP6c or PP6R1 led to sustained H2AX levels after IR, whereas inhibition of PP6c or PP6R2 expression, but not PP6R1 expression, resulted in sustained H2AX levels after CPT treatment [102].…”
Section: Phosphatases For γH2axmentioning
confidence: 99%
See 2 more Smart Citations